COMPARATIVE STUDY ON THE FIGHT FOR LOVE IN THOMAS HARDY’S THE WELL-BELOVED, JOHN COLLIER’S THE CHASER, AND JESSE STUART’S LOVE - Abu Fanani; Nur Mufid; Akhmad Syaikhu; Ahmad Frank; Abdur Rohman (Lingustic, Literature and English Education, 2026)
This study is about the fight for love in three fictions, two of which belongs to short stories, in Thomas Hardy’s the Well-Beloved, John Collier’s the Chaser, and Jesse Stuart’s Love. Using the concept of romance quoted by Shumway supported by close reading as well as descriptive and dramatic approach, the study shows that the three characters in three different fictions fight for love for different importance; the former for the holy matrimony, the latter for himself, and the last for others. Whilst, the similarities go to the valuable thing they sacrifice, on one hand. On the other hand, the difference goes to sacrificing the whole life time, his valuable love, and their life, respectively. Besides, the study gives a lesson that love can be sacrificed for others and ourselves.